Mini-Review: brown macroalgae as a promising raw material to produce biostimulants for the agriculture sector - Kergosien, Nolwenn; Stiger-Pouvreau, Valérie; Connan, Solène; Hennequart, Franck; Brébion, Jérémy (Frontiers in Agronomy, 2023)
The worldwide growing food demand and the excessive use of synthetic and chemical inputs compel the agricultural sector to find innovative and sustainable solutions to enhance or at least maintain crop yields in times of increased abiotic stresses levels linked to global change. Currently, great research efforts are carried out on brown seaweeds as their environment lead them to produce a broad range of compounds, with osmoregulatory, antioxidant, pro-bacterial, and plant-growth promoting activities. Indeed, numerous studies are looking at different combinations of algal species, extraction processes, plant species and environments of plant culture to highlight the various effects of algal extracts on plant growth and development, and resistance to abiotic stresses. Consequently, a wide variety of novel commercial products are emerging, presenting diversified chemical compositions, formulations and means of application. Such products allow the biostimulation of plants and soil by alleviating abiotic stresses such as drought, frost, and salt. The action of brown macroalgal extracts on plant and soil health has been repeatedly demonstrated, yet the precise relation between the extract chemical composition and its subsequent effect is still to be elucidated, as molecular synergy is suspected to play an important role. In this review, we present the interest of using brown macroalgal extracts to produce biostimulants with beneficial action on soil health, plant growth and development, as well as resistance against abiotic stresses, in relation to the molecular changes occurring.